A color-blind Lens: public perceptions of systemic racism in the criminal justice system - Dunbar, Adam (Crime, law and social change, 2023)
Extensive research has explored public confidence in the criminal justice system and opinions about punishment, but less research has explored attitudes about criminal justice errors, including error related to race and racism. Drawing on the theory of colorblind racism, the current study examines attitudes about whether systemic racism exists in the criminal justice system and, if so, how the issue can best be addressed. Specifically, we examine the rhetoric respondents use to describe the role of systemic racism in the criminal justice system, paying particular attention to the presence of colorblind rhetorical frames. Findings indicate that although a majority of respondents believe systemic racism exists, many respondents attribute the problem to specific individuals or policies rather than institutions and organizations. Moreover, those who believe systemic racism does not exist often rely on colorblind rhetorical frames that justify or minimize existing racial disparities in criminal justice outcomes. These findings suggest reasons for optimism regarding efforts to address racial injustice as well as some potential obstacles.